CHRONIC HEART FAILURE AS A TOPICAL CARDIOVASCULAR PATHOLOGY IN THE ADULT POPULATION - Kityan Sergey Alexandrovich (Scholar Express Journals, 2024)
Chronic heart failure is a syndrome that develops as a result of impaired ability of the heart to fill and/or empty, proceeding in conditions of impaired balance of vasoconstrictor and vasodilating neurohormonal systems, accompanied by inadequate perfusion of organs and tissues of the body and manifested by a complex of symptoms: dyspnoea, weakness, palpitations, increased fatigue and fluid retention in the body (oedema syndrome).
Keywords: chronic heart failure; vascular pathology